1979
DOI: 10.1111/j.1399-3054.1979.tb02623.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Study of Douglas‐fir Pollen Germination in vitro

Abstract: Douglas‐fir [Pseudotsuga menziesii (Mirb.) Franco] pollen was germinated and grown in mass in a sterile mineral medium supplemented with 0.3 M mannitol as osmotic stabilizer. During the 4‐day period, pollen elongated threefold; free sugar and amino acid contents did not change significantly; soluble protein, insoluble protein, and RNA decreased; starch reduced to 30%; and DNA doubled in quantity. Respiration rate remained high and constant during the first 36 h and then increased, but the respiratory quotient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Mais il est clair qu'une telle évolution ne pourrait être instantanée. Comme chez plusieurs autres espèces, (D UFFfELD & S NOW , 1941 ;VISSER, 1955 ;K INC , t965 ;Jervsetv, 1970 ;GtLrssEH, 1977 ;M UREN et al., 1979) on voit donc que pour du pol!len conservé après déshydratation, la seule introduction de cette phase de réhydratation ménagée permet à certains lots de retrouver un taux élevé de germination. Cette constatation pourrait permettre d'améliorer les techniques de conservation en autorisant une déshydratation plus poussée que celle qui est actuellement conseillée.…”
Section: Resultsunclassified
“…Mais il est clair qu'une telle évolution ne pourrait être instantanée. Comme chez plusieurs autres espèces, (D UFFfELD & S NOW , 1941 ;VISSER, 1955 ;K INC , t965 ;Jervsetv, 1970 ;GtLrssEH, 1977 ;M UREN et al., 1979) on voit donc que pour du pol!len conservé après déshydratation, la seule introduction de cette phase de réhydratation ménagée permet à certains lots de retrouver un taux élevé de germination. Cette constatation pourrait permettre d'améliorer les techniques de conservation en autorisant une déshydratation plus poussée que celle qui est actuellement conseillée.…”
Section: Resultsunclassified
“…v Discussion Pollen viability, elongation and tube growth Using Douglas fir pollen grains, Ho and Sziklai (1972) showed that a 1:10 dilution of Brewbaker and Kwack (BK) medium was more effective than full strength, and that optimum pollen viability was achieved by supplementing the medium with 10% sucrose and 10 ppm IAA. Muren et al (1979) reported improved pollen viability using mannitol, and showed that it is superior to sucrose as an osmotic regulator. However, Webber and Bonnet-Masimbert (1993) obtained better results using diluted BK medium supplemented with 10% sucrose and varying levels of polyethylene glycol (PEG).…”
Section: Female Gametophyte Viability and Penetrationmentioning
confidence: 99%
“…When cultivated in vitro, pollen of many coniferous plants germinates during 1–2 days. Protocols have been developed for many species [ 26 , 27 , 28 ], allowing efficient pollen germination and monitoring of its behavior for a long time. The studies of conifer pollen tubes in vitro revealed their differences from the tubes of angiosperms, including cytoskeleton organization, regulation of organelle movement, and endo/exocytosis [ 5 ], which we will discuss in the next section.…”
Section: Pollination and Pollen Germination In Gymnosperm Speciesmentioning
confidence: 99%
“…Germination occurs slower in Douglas fir ( Pseudotsuga menziesii) than in pine and spruce [ 28 ]. Respiration remained high and constant during the first 36 h, and then increased sharply (apparently due to the germination), while ATP content increased rapidly already during the first 8 h and remained high until the end of the observation period [ 28 ]. During the first 24 h in culture, ATP content increased by 86%, while the content of ADP and AMP decreased.…”
Section: Biochemical Regulation Of Conifer Pollen Germination and Pollen Tube Growthmentioning
confidence: 99%